PKIUSM ETCHES ITS NAME INTO THE MALAYSIA BOOK OF RECORDS FOR THE LARGEST OIL LAMP FORMATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 1 March 2016 The Universiti Sains Malaysia (USM) marching field (Padang Kawad USM) was a spectacle of lights last Saturday when members of the USM Indian Cultural Society (Persatuan Kebudayaan India – PKIUSM) successfully created the largest logo using Indian oil lamps.